GA2LEN ANACARE consensus statement: Potential of omalizumab in food allergy management - Torsten Zuberbier; Antonella Muraro; Ulugbek Nurmatov; Stefania Arasi; Katarina Stevanovic; Aikaterini Anagnostou; Roberta Bonaguro; Sharon Chinthrajah; Gideon Lack; Alessandro Fiocchi; Thuy‐My Le; Paul Turner; et al. (Clinical and Translational Allergy)
Abstract Immunoglobulin E (IgE)‐mediated food allergies are the most common type of food allergy, often causing rapid symptoms after exposure to allergens posing a serious health risk and a high impact on patient's and caregiver's quality of life. Omalizumab, a humanized anti‐IgE monoclonal antibody, reduces allergic reactions by binding to circulating IgE. Omalizumab has been successfully used in allergic asthma, chronic rhinosinusitis with nasal polyps, and chronic urticaria, and was recently approved for treating IgE‐mediated food allergies by the US Food and Drug Administration (FDA). This GA2LEN ANACARE Consensus Statement presents our position on the use of omalizumab for treating IgE‐mediated food allergies, based on a systematic review and meta‐analysis, experience with use for other conditions, and expert consensus achieved via an eDelphi process. Following publication of the recent OUtMATCH study (stage 1) results and subsequent FDA approval, we propose that there is now sufficient evidence to recommend omalizumab as the only drug currently available that can mechanistically reduce IgE‐mediated food allergic reactions. We acknowledge that the evidence does not reach the highest level of evidence which would be needed for a guideline recommendation.